Riboswitch Discovery, Structure and Function - Burke, Donald H. (Methods in enzymology, 2014)
This volume covers research methods in riboswitch discovery and validation, synthesis and sample prep methods for large RNAs, riboswitch structure and function methods, folding pathways and dynamics, and ligand interactions and thermodynamics. Continues the legacy of this premier serial with quality chapters authored by leaders in the fieldCovers research methods in biomineralization science. Contains sections on such topics as riboswitch discovery and valid.